Prevalence of phantom vibration syndrome and its associated factors among undergraduate students in a public university - Hamdan, Abu Bakar; Mohd Zulkefli, Nor Afiah; Ahmad Fauzi, Fatimah (Elsevier B.V., 2025)
Background: Phantom Vibration Syndrome (PVS) is a unique and interesting phenomenon caused by the widespread use of smart devices where individuals perceive vibrations from their smart devices when none are occurring. It is classified as a tactile hallucination because the brain interprets an absent sensation. This study highlights the importance of urgency in dealing with this issue in our technologically advanced society by providing useful information for both scholarly discussion and real-life use in the digital age. Objectives: This study was conducted to determine the prevalence of PVS and its associated factors, which include sociodemographic characteristics, device characteristics, device usage patterns, smartphone addiction, and mental health. Methodology: A cross-sectional study was conducted using a validated questionnaire among undergraduate students in a public university in Malaysia, who were identified using proportionate stratified random sampling. The dependent variable measured through the questionnaire was the prevalence of PVS, while the independent variables were socio-demographic factors (age, gender, ethnic), device characteristics (types of devices, device location, notification alert in vibration mode and regularity in using vibration mode), device usage patterns (frequency, duration and purpose of using devices), smartphone addiction, and mental health (perceived stress, anxiety and depression). Data were analyzed using IBM SPSS application version 29. Results: A total of 381 responses were obtained, with response rate of 92.7%. The mean age of respondents was 21.96 ± 1.64 years. The prevalence of PVS was 49.3%, which was predicted by age (AOR: 0.55; 95%CI: 0.38–0.95), location of device carried in the front pocket of pants (AOR: 0.58; 95%CI: 0.36–0.95), location of device carried in sling bag (AOR: 0.49; 95%CI: 0.32–0.77), notification alert in vibration mode (AOR: 2.33; 95%CI: 1.33–4.09) and regularity using vibration mode (AOR: 2.91; 95%CI: 1.84–4.61). Conclusion: Five factors predicted PVS in this study, comprising one sociodemographic variable and 4 device characteristics variables. Based on the results, health education should teach undergraduate students to recognize PVS symptoms and implement healthy technology practices such as optimizing device placement, decreasing vibration mode usage, and regulating device usage behaviors. Practical advice on setting limits and taking breaks can also reduce PVS risk.